2016
DOI: 10.1002/aenm.201600108
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylferrocene)–Reduced Graphene Oxide as a High Power/High Capacity Cathodic Battery Material

Abstract: The preparation and performance of a new cathodic battery material consisting of a composite of poly(vinylferrocene) (PVFc) and reduced graphene oxide (rGO) is described. It shows the highest charge/discharge efficiency (at a rate of 100 A g−1) ever reported for ferrocene–polymer materials. The composite allows for specific capacities up to 0.21 mAh cm−2 (770 mC cm−2, 29 μm film thickness) at a specific capacity density of 114 mAh g−1 and less than 5% performance decay over 300 cycles. The composite material i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 86 publications
0
57
0
Order By: Relevance
“…Polymers with ferrocene-containing side chains show useful properties including air stability, fast electrochemical kinetics, and stable voltage plateaux for the development of cathodic battery materials. [215][216][217][218][219][220] Such polymers are electrically insulating, however, which limits their use as energy storage materials to small thicknesses, because fast charging/discharging kinetics are required. The electronic conductivity can be enhanced, however, by introduction of conductive polymers.…”
Section: Ferrocene Polymers For Cathodic Battery Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers with ferrocene-containing side chains show useful properties including air stability, fast electrochemical kinetics, and stable voltage plateaux for the development of cathodic battery materials. [215][216][217][218][219][220] Such polymers are electrically insulating, however, which limits their use as energy storage materials to small thicknesses, because fast charging/discharging kinetics are required. The electronic conductivity can be enhanced, however, by introduction of conductive polymers.…”
Section: Ferrocene Polymers For Cathodic Battery Materialsmentioning
confidence: 99%
“…[216] Ferrocene polymers have also been used as battery materials after carbon fillers were loaded into the polymer matrixes. [217][218][219][220] Walder's group recently reported a way to disperse negatively charged graphene oxide (GO) single sheets with partially oxidized poly(vinylferrocene) through electrostatic interactions with use of polymer/GO weight ratios of up to 10:1. Remarkably, these authors found that a film of (PVFc@rGO)@CC (current collector) with a specific capacity of 5.8 mC cm -2 was >98 % charged/discharged in less than 3 s, and that increasing the layer thickness up to ca.…”
Section: Ferrocene Polymers For Cathodic Battery Materialsmentioning
confidence: 99%
“…The changesi np olarity prior to and after oxidation of PVFc was used to achieve molecularly tightly connected graphene sheets-metallopolymer strands. [72] For this purpose, the nega-tively charged graphene oxide and partially oxidized, positively chargedP VFc was used. Mesoporousc omposite structures featuring ion percolating properties were accessible for the preparation of metallopolymer battery applications.…”
Section: Redox-triggered Surface Properties Of Ferrocene-containing Pmentioning
confidence: 99%
“…In the recent past, the interesting ferrocene/ferrocenium redox couple in metallopolymers has attracted significant interest due to the unique ability to (electro)chemically switch between hydrophobic ferrocene and comparably hydrophilic ferrocenium moieties . Moreover, such types of metallopolymers revealed an excellent combination of (switchable) redox, mechanical, semi‐conductive, photo‐physical, optoelectronic, magnetic, and catalytic properties . A very recent review highlighting the progress of metallopolymers in the field of biomedical applications is given by Tang and co‐workers .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Moreover, such types of metallopolymers revealed an excellent combination of (switchable) redox, mechanical, semi-conductive, photo-physical, optoelectronic, magnetic, and catalytic properties. [16][17][18][19][20][21] A very recent review highlighting the progress of metallopolymers in the fi eld of biomedical applications is given by Tang and co-workers. [ 22 ] Since A convenient synthetic approach for the preparation of uniform metallopolymer-containing hollow spheres based on 2-(methacryloyloxy)ethyl ferrocenecarboxylate (FcMA) as mono mer by sequential starved feed emulsion polymerization is described.…”
mentioning
confidence: 99%